A simple microeconomic model for the analysis of Vollgeld - Peter Bofinger; Thomas Haas (University of Würzburg, Department of Economics, 2018)
In June 2018 the"Vollgeld" initiative will be submitted to the Swiss people. We contribute to the ongoing discussion of a sovereign money system, by providing a price-theoretic model for the money supply under a "Vollgeld"-system. As banks would no longer have the ability to create money, they are merely intermediaries of funds. The central bank would be the only institution to create money. But the central bank is no longer the only supplier of monetary base for the banking sector on the money market. Banks could also lend from the public and private sector. As the analysis of our model shows,the degree of instability would increase under the "Vollgeld"-system and result in higher interest rate volatility.
Keywords: E51; E52; 330; money supply process; monetary theory; sovereign money